The Xingguang-III laser facility: precise synchronization with femtosecond, picosecond and nanosecond beams. (4th December 2017) - Zhu, Qihua; Zhou, Kainan; Su, Jingqin; Xie, Na; Huang, Xiaojun; Zeng, Xiaoming; Wang, Xiao; Wang, Xiaodong; Zuo, Yanlei; Jiang, Dongbin; Zhao, Lei; Li, Fuquan; et al.
Abstract: We report a high-intensity laser facility named Xingguang-III that generates femtosecond, picosecond, and nanosecond beams with three wavelengths, i.e. 800 nm, 1053 nm, and 527 nm, respectively. To the best of our knowledge, the laser facility is the first one which produces three beams with different pulse widths and wavelengths. An optical synchronization technique, combining super continuum generation and femtosecond optical parametric amplification, was developed to ensure three beams are from the same source to achieve precise synchronization. The femtosecond beam is a double chirped-pulse-amplification Ti:sapphire laser which applies cross-polarized wave generation to improve the temporal contrast. The picosecond/nanosecond beams utilize the optical parametric amplification  +  Nd:glass mixed amplification scheme. The output energy and pulse width of the three beams are 20.1 J/26.8 fs, 370.2 J/0.48 ps (shortest), and 575.4 J/1.0 ns, respectively. The smallest synchronization time (peak-to-valley) and the shot-to-shot timing jitter (peak-to-peak) of less than 1.32 ps have been achieved for the femtosecond and picosecond beams.